Auditoría tributaria a la Caja Comunal San Francisco de Salinas para determinar el grado de cumplimiento de las obligaciones fiscales en el período 2022 - Collay Yanchaliquin, Marcelo Hernan (2024)
The objective of this work was to carry out a Tax Audit of the Caja Comunal San Francisco de Salinas, in order to provide the audit report and the good practices manual that promotes a tax culture. Descriptive research was used with a quantitative and qualitative approach, of a non-experimental and field type, using data collection methods such as survey and interview, using research tools such as the questionnaire and interview guide, with the purpose to obtain meaningful information; The data was collected through a survey carried out on people who make up the Caja Comunal San Francisco de Salinas, the interview was carried out with its manager. During the execution of the Tax Audit, it was possible to diagnose and verify the declarations and annexes presented, through which findings were found such as delays in the monthly VAT declarations presented to the tax administration, information with the necessary support and the non-presentation of the Annex to financial accounts of non-residents. It was determined that there is a lack of tax awareness and staff training. Therefore, it is suggested that the Community Fund carry out training for its staff, either using internal resources or requesting assistance from the Internal Revenue Service.